Phylogeny of Holothuria leucospilota (Echinodermata: Holothuroidea) as inferred from cytochrome c oxidase I gene sequences - Idris, Mohd Yaman; Ahmad, Hajar Fauzan; Hashim, Ridzwan; Usup, Gires; Kamarudin, Kamarul Rahim; Mohamed Rehan, Aisyah (2010)
This study aims to determine the phylogenetic relationship between Holothuria leucospilota (Echinodermata: Holothuroidea) from Malaysia and other Holothuria species using partial sequences of cytochrome c oxidase I (COI) mitochondrial DNA (mtDNA) gene. Holothuria (Mertensiothuria) leucospilota (Brandt, 1835) or locally known as bat puntil is currently the most abundant sea cucumber species in Malaysia. This coral reef species is not in danger of extinction like commercial Stichopus species that are locally known as gamat such as Stichopus horrens. Previously, COI mtDNA gene sequences of H. leucospilota were unavailable online in GenBank, National Center for Biotechnology Information (NCBI); thus leading to this phylogenetic study. In this study, specimens of H. leucospilota were collected from Intan Besar Island, Langkawi, Malaysia. Eight COI mtDNA gene sequences of H. leucospilota obtained from this study have been registered with the GenBank (Accession no.: FJ223873 - FJ223880, submission date: 19 September 2008). Three main methods namely neighbour joining, maximum parsimony and maximum likelihood were used for phylogenetic tree reconstruction. Present results showed that H. leucospilota was genetically closer to H. coluber as compared to H. atra. Even so, further studies with more samples, broad geographical sampling and various mitochondrial DNA genes are necessary to obtain better information and verification on molecular phylogeny of H. leucospilota in particular and Holothuria species in general.